2019
DOI: 10.1177/1120672119841002
|View full text |Cite
|
Sign up to set email alerts
|

A triad of retinal signs in Alport syndrome: The ‘stair-case’ fovea, choroidal thinning and peripheral schisis

Abstract: Background: Alport syndrome is an inherited Type IV collagenopathy characterised by renal failure, hearing loss and ophthalmic manifestations such as lenticonus and dot-and-fleck retinopathy. New signs have been described which can be useful both for diagnosis and for prognosticating the risk of complications. This study examines and describes a triad comprising the unusual ‘stair-case’ foveal sign, together with choroidal thinning and late-stage peripheral schisis in a patient with Alport syndrome. Case prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…No treatment was reported in this case report. Ghadiri et al [ 35 ] reported a case in a middle-aged Caucasian male patient who presented with unusual symptoms in his left eye that was described as the same triad of features reported in Stanojcic et al: “stair-case” fovea, choroidal thinning, and peripheral retinoschisis. These signs were associated with unique mutations in COL4A5 .…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…No treatment was reported in this case report. Ghadiri et al [ 35 ] reported a case in a middle-aged Caucasian male patient who presented with unusual symptoms in his left eye that was described as the same triad of features reported in Stanojcic et al: “stair-case” fovea, choroidal thinning, and peripheral retinoschisis. These signs were associated with unique mutations in COL4A5 .…”
Section: Resultsmentioning
confidence: 79%
“…AS ocular effects have yet to be proven to be alleviated by surgical approaches, such as vitrectomies, cataract surgeries, and IM peeling [ 29 , 32 , 35 , 37 , 38 , 47 ]. These techniques have been used to help target ocular findings and complications in non-AS patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In AS, the embryonic collagen IV structure (α1α1α2) is not replaced by the mature one (α3α4α5), which results in an increased susceptibility to proteolysis and lesions in tissues rich in type IV collagen (glomerulus, cochlea, cornea, lens, and retina) [3,4]. This disease exhibits variability in its clinical and pathological manifestations and is genetically heterogeneous [5]. About 85% of the AS patients have X-linked inheritance due to mutations in COL4A5, on X chromosome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being considered a renal disease, 40% of patients present ocular defects as early signs, even preceding proteinuria [9]. The mutation in collagen IV α3α4α5 network caused basement membrane thinning, lamellation, and rarefaction, alongside the intraocular mechanical stresses [5]. Among the broad spectrum of possibilities for ocular manifestations, some could be highlighted, concerning the cornea, lens, and retina.…”
Section: Introductionmentioning
confidence: 99%